Nanofiltration desalination of reverse osmosis concentrate pretreated by advanced oxidation with ultrafiltration: Response surface optimization and exploration of membrane fouling. Issue 6 (December 2021) - Song, Wanchao; Li, Na; Ding, Shaoxuan; Wang, Xiaoyan; Li, Huawei; Zhang, Yonghui; Feng, Xuedong; Lu, Jie; Ding, Jincheng
Abstract: Reverse osmosis (RO) technique has been widely used in the advanced treatment of industrial water and wastewater. However, this process generates a large amount of reverse osmosis concentrate (ROC) which contain high salinity and organic contaminants, and therefore pose serious environmental problems. This study explored the potential of advanced oxidation processes-ultrafiltration (AOPs-UF) pretreatment system and nanofiltration (NF90, Dow Chemicals) membrane system for ROC desalination. Under the optimal conditions, 78% of COD and 81% of UV254 pollutants were removed by using advanced oxidation processes with ultrafiltration pretreatment technology. Box-Behnken design (BBD) results showed that the maximum total soluble salts rejection of 97.75% was obtained under the optimized conditions of nanofiltration membrane (the 1.18 MPa operating pressure, 6.79 °C feed temperature, 64.33 min filtration time). A combined membrane cleaning method was finally determined via surface morphology characterization by the comparison of scanning electron microscope (SEM), X-ray energy dispersive analysis (EDS) and Fourier transform infrared (FTIR) technique analysis. The results confirmed the possibility of advanced oxidation coupled membrane treatment process to treat ROC and realize its reuse. Moreover, by evaluating the benefit calculation, it provides insights for the treatment of industrial wastewater. Graphical Abstract: ga1 Highlights: AOPs-UF is an effective pretreatment for NF desalination of high-salinity ROC. RSM was used for analysis and optimization of the NF experimental conditions. At optimum conditions, 97.75% of total soluble salts rejection was obtained. Predicted and validated values were in close agreement with each other. The data showed that RSM is suitable for optimizing NF desalination of ROC.